Impact of Flow Velocity on Transport of Graphene Oxide Nanoparticles in Saturated Porous Media - Zhang, C. (2020)
In contrast, the presence of nanoscale protruding asperities (NPAs) can cause a decrease in the energy barrier with increasing IS, which facilitates the attachment in primary minima at higher IS. At a given IS, increasing flow velocity increases attachment efficiency on the rough sand surfaces. Torque analysis shows that the maximum hydrodynamic torques are smaller than the adhesive torques, even for GONPs located on the NPAs where the adhesions are the lowest. Consequently, the attachment efficiency cannot be reduced by increasing flow velocity. Additional column experiments confirm that deposited GONPs cannot be detached by increasing flow velocity. Conversely, increase of flow velocity may enhance approaching of GONPs in low‐flow regions such as concave areas of sand surfaces and subsequent attachment. Although it has been recognized in the literature that the presence of NPAs can cause decrease of attachment efficiency with increasing flow velocity for spherical colloids under both unfavorable and favorable chemical conditions, our results highlight a different role of surface roughness in attachment and detachment of sheet‐shaped colloids under unfavorable conditions.